Boys, Girls, and the Second Shift: Paid and Unpaid Labor in High School and Adolescents' Enrollment in College. (April 2018) - Obach, Heidi; Li, Angran; Cheng, Simon
Sociological research examines the gender gap reversal in higher education and the gender division in paid and unpaid labor for adult women, especially "the second shift literature, " as two distinct topics. In this study, we extend the insights of the second shift literature to research on youth labor and adolescents' enrollment in higher education. Using data from the Youth Development Study from 1988 to 1992, we find that the negative association of unpaid labor with adolescents' college enrollment odds was at least as large as, if not greater than, that of paid labor. Although labor engagement had adverse impacts both for female and male adolescents during this time, the negative associations of youth labor with college enrollment were more pronounced for male students. We discuss the implications of these findings and explain their relevance to more contemporary cohorts of high school students in the conclusion.